Prognostic value of D-dimer in treatment and follow up for patients who underwent radiotherapy in advanced lung cancer - Huriye Senay Kiziltan; Kimia Cepni (PLoS ONE, 2025)
Background Lung carcinma, a serious disease commonly recognized at advanced stages and has less favorable outcomes to treatments. This research examines the association between D-dimer values and clinical variables in patients diagnosed with advanced lung cancer, with a focus on their prognostic significance and radiotherapy related outcomes. Methods This retrospective observational descriptive cohort study, including 142 patients with lung cancer. Aa comprehensive analysis, was conducted, including demographic variables,clinical staging, pathology, laboratuary tests, and D-dimer levels measured both before and after the administration of radiotherapy. Results The findings indicated that high pre-RT D-dimer concentrations were significantly assoccciated with advanced stages of disease, worse response of radiotherapy, Eastern Cooperative Oncology Group performance status, and decreased survival outcomes. Radiotherapy response also affects to survival rates with D-dimer values. The findings from both univariate and multivariable survival analyses demonstrated that lower concentrations of D-dimer correlated with better response of radiotherapy, extended overall survival and progression free survival (p: < 0.001). Conclusion These results illustrate the significant role of D-dimer as a valuable biomarker for assessing tumor burden and guiding radiotherapy and other treatment strategies in lung cancer, thereby necessitating further inquiry to evaluate its clinical implications.